Preliminary study on the explosive performance of coal dust and prospects for engineering applications - Jing Guo; Shirong Ge (Scientific Reports)
Abstract This study aims to evaluate the efficiency and energy release characteristics of different types of coal in pulse detonation engines (PDE) to advance the development of deep coal fluidization detonation technology, achieving more efficient and cleaner coal utilization. Using a custom PDE setup, experiments were conducted with four coal types at mass flow rates from 30 to 120 g/s. High-frequency pressure sensors assessed pressure dynamics and detonation wave propagation, complemented by numerical simulations for accuracy. Results show that the maximum detonation pressure (Pmax) increases linearly with coal mass flow, with anthracite reaching 1.52 MPa at 120 g/s. A consistent linear relationship between Pmax and maximum temperature (T max) was observed. Detonation combustion efficiency (η DCE) improved with mass flow, with peat rising from 52.3% to 83.7%. These findings provide a foundation for advancing deep coal fluidized detonation technology, contributing to more efficient and cleaner coal utilization.